Pemetaan Pola Permohonan dan Putusan dalam Pengujian Undang-Undang dengan Substansi Hukum Islam - Dian Agung Wicaksono; Faiz Rahman; Khotibul Umam (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
The existence of Islamic law substance in national law, specifically in an Act, has been indirectly placed the Constitutional Court in the position that also has a role in determining the development of Islamic law in the national law system. It can be seen in the context of judicial review of Act that has Islamic law substance or that explicitly regulates Islamic law. This research specifically answers: (a) how is the justification of the inclusion of Islamic law in Indonesian national law? (b) how are the pattern of judicial review petitions and court decisions of Acts related to Islamic law? This research is normative-juridical research, which analyses secondary data such as laws and regulations, Constitutional Court decisions, and articles related to the inclusion of Islamic law in the national law. The results show that the justification of the accommodation of Islamic law in the national law system is related to the construction of state and religion relationship. It indicates that Indonesia is not a religious state, but it is a state that has a divine principle. Furthermore, based on the analysis of judicial review decisions from 2003 to 2019, the pattern of petitions and court decisions of judicial reviews of laws related to Islamic law substance shows at least three main petitions, namely: (a) questioning state intervention in the implementation of Islamic law; (b) questioning the administration of the implementation of Islamic law; (c) petitions for the inclusion of Islamic law in the positive law.